IDENTIFIKASI KEBERAGAMAN PESERTA DIDIK SEBAGAI DASAR IMPLEMENTASI PENDIDIKAN INKUSIF: KAJIAN LITERATUR PSIKOLOGI PENDIDIKAN - Thahir, Rahmatia; Zaitun, Zaitun; Anisa, Anisa; Azis, Fatimah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Inclusive education positions learner diversity as the main strength in the learning process, encompassing students with special needs as well as differences in learning styles, cognitive abilities, socio-emotional characteristics, and cultural backgrounds. In the practice of inclusive education, a commonly encountered problem is the suboptimal process of identifying learner diversity as the basis for instructional design; therefore, this study analyzes the utilization of the identification process in designing effective and equitable inclusive learning. This study employs a literature review method with a descriptive qualitative approach through stages of searching, selection, and content analysis of national and international scholarly articles published over the past ten years. The findings indicate that the success of inclusive education is influenced by educators’ ability to understand individual learner characteristics through continuous identification processes. The challenges faced include limitations of identification instruments, diverse teacher competencies, inadequate policy support, and limited parental involvement. To address these challenges, the implementation of instructional strategies such as differentiated instruction, Universal Design for Learning (UDL), and collaborative approaches is considered effective in accommodating learner diversity. The conclusion of this study emphasizes that the identification of learner diversity is a key element in realizing humanistic, equitable, and transformative education. ABSTRAK Pendidikan inklusif menempatkan keberagaman peserta didik sebagai kekuatan utama dalam proses pembelajaran yang mencakup peserta didik berkebutuhan khusus serta perbedaan gaya belajar, kemampuan kognitif, karakter sosial-emosional, dan latar belakang budaya. Dalam praktik pendidikan inklusif, permasalahan yang sering dijumpai adalah belum optimalnya proses identifikasi keberagaman peserta didik sebagai dasar perancangan pembelajaran; oleh karena itu, kajian ini menganalisis pemanfaatan proses identifikasi tersebut dalam merancang pembelajaran inklusif yang efektif dan berkeadilan. Penelitian ini menggunakan metode studi literatur dengan pendekatan kualitatif deskriptif melalui tahapan penelusuran, seleksi, dan analisis isi terhadap artikel ilmiah nasional dan internasional dalam sepuluh tahun terakhir. Hasil kajian menunjukkan bahwa keberhasilan pendidikan inklusif dipengaruhi oleh kemampuan pendidik dalam memahami karakteristik individual peserta didik melalui proses identifikasi yang berkelanjutan. Tantangan yang dihadapi meliputi keterbatasan instrumen identifikasi, kompetensi guru yang beragam, dukungan kebijakan yang belum optimal, serta keterlibatan orang tua yang terbatas. Untuk merespons tantangan tersebut, penerapan strategi pembelajaran seperti differentiated instruction, Universal Design for Learning (UDL), dan pendekatan kolaboratif dinilai efektif dalam mengakomodasi keberagaman peserta didik. Simpulan kajian ini menegaskan bahwa identifikasi keberagaman peserta didik merupakan elemen kunci dalam mewujudkan pendidikan yang humanis, adil, dan transformatif.